Teaching practice as a component of teacher education in Malawi: an activity theory perspective - Mtika, Peter David Galimoto (2008)
This qualitative research is an exploration of the experiences of student teachers during teaching practice as a component of initial teacher education in Malawi. The research was necessitated by a general lack of knowledge about secondary school teacher education in Malawi and the view that teaching practice is one of the major components of concern for professional learning among student teachers. An activity theory perspective provided a theoretical and conceptual lens of understanding teaching practice. The elements within activity theory which were of particular significance related to tools/artefacts, subjects, objects and outcomes in teaching practice; rules/norms within an activity system of teaching practice; perceptions of individuals about teacher education and a teaching activity; pedagogical actions and understanding during teaching practice; the community relationships in school systems where student teachers carried out teaching practice; division of tasks; activity settings; tensions/contradictions, as well as innovations within the activity of teaching practice (Engestrom, 1999). The participants in the study were drawn mainly from student teachers on a three-year teacher education programme at one of the teacher education institutions in Malawi.